2021
DOI: 10.1038/s41598-021-82174-8
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the deep carbon cycle from the electrical conductivity of carbon-bearing aqueous fluids

Abstract: The dehydration and decarbonation in the subducting slab are intricately related and the knowledge of the physical properties of the resulting C–H–O fluid is crucial to interpret the petrological, geochemical, and geophysical processes associated with subduction zones. In this study, we investigate the C–H–O fluid released during the progressive devolatilization of carbonate-bearing serpentine-polymorph chrysotile, with in situ electrical conductivity measurements at high pressures and temperatures. The C–H–O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…The electrical conductivity measurement is a very efficient approach to trace the state change (e.g., dehydration, dehydrogenation, decarbonation, melt, phase transition, etc.) of the sample at high temperature and high pressure, since a slight change of sample state usually can cause an observable variation in conductivity with temperature or pressure (Maumus et al, 2005;Manthilake et al, 2016;Hu et al, 2017;Hu et al, 2018;Manthilake et al, 2021;Hong et al, 2022). In this study, the sudden change in the conductivity occurred 350-450 °C at different pressure has demonstrated that the siderite sample underwent a low degree decarbonation, producing magnetite and graphite that confirmed and quantified by confocal Raman imaging and TIMA image.…”
Section: Constraints On the Incipient Temperature Of Siderite Decarbo...supporting
confidence: 66%
See 1 more Smart Citation
“…The electrical conductivity measurement is a very efficient approach to trace the state change (e.g., dehydration, dehydrogenation, decarbonation, melt, phase transition, etc.) of the sample at high temperature and high pressure, since a slight change of sample state usually can cause an observable variation in conductivity with temperature or pressure (Maumus et al, 2005;Manthilake et al, 2016;Hu et al, 2017;Hu et al, 2018;Manthilake et al, 2021;Hong et al, 2022). In this study, the sudden change in the conductivity occurred 350-450 °C at different pressure has demonstrated that the siderite sample underwent a low degree decarbonation, producing magnetite and graphite that confirmed and quantified by confocal Raman imaging and TIMA image.…”
Section: Constraints On the Incipient Temperature Of Siderite Decarbo...supporting
confidence: 66%
“…Frontiers in Earth Science frontiersin.org (magnetite and graphite) generated from the siderite component of the Fe-bearing carbonate, into serpentinite will improve the interconnectivity of magnetite, that likely become the origin of highly conductivity anomalies observed in the slab-mantle wedge interface at relatively shallow depth of ~20-40 km. As the plate subducts downwards, besides the progressive decarbonation of Fe-bearing carbonate, the dehydration of hydrous minerals, e.g., chlorite (Manthilake et al, 2016) and epidote (Hu et al, 2017), as well as devolatilization of carbonate-bearing serpentinite (Manthilake et al, 2021) can provide substantial iron oxides (e.g., hematite, magnetite). The accumulation of iron oxides at the slab-mantle wedge interface is potentially responsible for the anomalous high conductivity observed at relatively deep depths.…”
Section: Implications For High Conductivity Anomalies At Slab-mantle ...mentioning
confidence: 99%
“…The sample length and diameter measured before the experiment were ~1.7 mm in length and ~1.0 mm in diameter. Similar aspect ratios have been successfully used in previous electrical conductivity measurements, particularly when the samples are cored out of natural rocks rather than synthesized using hot-pressed methods from powdered samples (Manthilake et al, 2015(Manthilake et al, , 2016(Manthilake et al, , 2021). After we recovered the sample, we measured the sample length ~1.7 mm, i.e., it remained unchanged.…”
Section: Methodsmentioning
confidence: 96%
“…The observed electrical conductivity anomalies in subduction zone settings are often linked with the presence of aqueous fluids (McGary et al, 2014). Support for this argument is further reinforced by numerous electrical conductivity studies based on laboratory experiments which demonstrate higher electrical conductivities for aqueous fluid compared to solid mineral phases (Manthilake et al, 2015(Manthilake et al, , 2016(Manthilake et al, , 2021bReynard et al, 2011;Shen et al, 2020;Wang & Karato, 2013;Wang et al, 2012;Zhang et al, 2014). Upon dehydration, the released fluids may lead to the formation of an interconnected network of a conductive phase (fluid/melt).…”
Section: Implications For the Wedge-mantle Electrical Anomaliesmentioning
confidence: 96%